Bacterial Isolation from Palm Oil Plantation Soil for Biodiesel Production: Isolation and Molecular Identification as Inferred by 16s RNA - Meng, Liu; M. M., Yusoff; Makky, Essam A.; Jailani, Salihon (JBTBM, 2014)
Biodiesel (methyl esters) is a clean alternative fuel which can be produced from many renewable resources. Palm oil, like other vegetable oils, can be used as feedstock for biodiesel production through transesterification to produce palm oil methyl ester. Various microorganisms like bacteria and fungi have a diversity application which could be used as catalysts in a series of degradation reactions, such as transesterification. Malaysia is rich in palm oil and therefore, lots of bacteria surviving by consuming palm oil residue resource in palm oil plantation. In this study, eighteen (18) bacterial strains were successfully isolated from local soil samples and some of their characteristics determined. The optimum temperatures of all strains were in the range of 30 to 37°C, and the optimum batch culture times of all strains were in the range of 24 to 48 hours. All strains were submitted for Gram-staining. Three (3) strains denominated as A, B and C that was involved in the most significant transesterification reaction was selected for identification by submitting them to biochemical tests using the commercial API kit. The same three (3) isolates were submitted to identification by molecular technique. Two bacteria were identified to be Pseudomonas geniculata (A) and Stenotrophomonas maltoplilia (C), while the second bacteria (B) identified to be Bacillus pseudomycoides B-60.